2013
DOI: 10.3389/fpls.2013.00051
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry, proteomics, and phosphoproteomics of plant mitochondria from non-photosynthetic cells

Abstract: Mitochondria fulfill some basic roles in all plant cells. They supply the cell with energy in the form of ATP and reducing equivalents [NAD(P)H] and they provide the cell with intermediates for a range of biosynthetic pathways. In addition to this, mitochondria contribute to a number of specialized functions depending on the tissue and cell type, as well as environmental conditions. We will here review the biochemistry and proteomics of mitochondria from non-green cells and organs, which differ from those of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 91 publications
2
26
0
Order By: Relevance
“…This should facilitate renewed plastid phosphorylation network analysis and linkage between (novel) plastid kinases, such as ABC1Ks (Lundquist et al, 2012) and candidate plastid substrates. According to a recent review (Havelund et al, 2013), 64 mitochondrial proteins (with 103 p-sites) were found to be phosphorylated. This number was increased to 168 proteins (from set A) in this study.…”
Section: Over-and Underrepresentation Of Phosphorylation In Cellular mentioning
confidence: 99%
“…This should facilitate renewed plastid phosphorylation network analysis and linkage between (novel) plastid kinases, such as ABC1Ks (Lundquist et al, 2012) and candidate plastid substrates. According to a recent review (Havelund et al, 2013), 64 mitochondrial proteins (with 103 p-sites) were found to be phosphorylated. This number was increased to 168 proteins (from set A) in this study.…”
Section: Over-and Underrepresentation Of Phosphorylation In Cellular mentioning
confidence: 99%
“…No studies to date have specifically examined the role of reversible protein phosphorylation in the mitochondrial IMS of any organism despite targeted proteomics studies revealing the presence of a number of protein kinases and protein phosphatases in this subcompartment (Salvi et al, 2005;Pagliarini and Dixon, 2006;Vögtle et al, 2012;Duncan et al, 2013). To date, 10 protein kinases have been localized to the plant mitchondrion, but none specifically to the IMS (Havelund et al, 2013). Furthermore, recent elucidation of the IMS proteome of yeast identified a number of IMS proteins that have been previously documented in whole mitochondria phosphoproteomics studies to be phosphorylated (Vögtle et al, 2012).…”
Section: Atslp2-atmia40 Protein Complex Negatively Regulates Ga Biosymentioning
confidence: 99%
“…In the intervening years, a number of more focused proteomic studies have been performed mainly on Arabidopsis mitochondria, swelling the number of identified plant mitochondrial proteins to 660 nonredundant proteins (Heazlewood et al, 2004;Duncan et al, 2011;Klodmann et al, 2011;Lee et al, 2012;Tan et al, 2012). Missing from this list are many essential plant mitochondrial activities, including regulatory proteins, transcription factors, metabolite translocators, and the wealth of tRNA synthases and pentatricopeptide repeat (PPR) proteins (Havelund et al, 2013).…”
mentioning
confidence: 99%